1984
DOI: 10.3758/bf03332158
|View full text |Cite
|
Sign up to set email alerts
|

Open-field social behavior in rats as a function of septal lesions in infancy and group versus isolated rearing conditions

Abstract: Normal rat pups and pups with septallesions produced at 7 days of age were reared after weaning under group and isolated housing conditions. Contact time between pairs of animals in the open fieldwas observed at 90·110days of age. Gregariousness was increased by both septaliesion treatment and isolated rearing conditions. The housing condition variable accounted for a greater proportion of treatment variance than did the lesion variable. These results stress the importance of housing conditions as a confoundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In summary, current and previous studies (e.g., Johnson et al, 1984) demonstrate that housing density during development can have a potent impact on the effects of open-field behaviors following septal lesions. This is observed in both hooded and albino rats, and is found whether surgery is performed in infancy or in adulthood.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In summary, current and previous studies (e.g., Johnson et al, 1984) demonstrate that housing density during development can have a potent impact on the effects of open-field behaviors following septal lesions. This is observed in both hooded and albino rats, and is found whether surgery is performed in infancy or in adulthood.…”
Section: Discussionsupporting
confidence: 53%
“…In a previous study (Johnson et al, 1984), we reported that open-field contact following septal lesions in infant hooded rats could be modified by the type of postweanIing housing maintained until observation. The present study demonstrates essentially the same pattern of results in albino rats when septal lesions are produced in adult animals following a developmental history of differential housing.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies in our laboratory (Johnson, Spiker & Carlson, 1984;Poplawsky & Johnson, 1973) as well as a number of studies at Ohio State (Jonason & Enloe, 1971;Meyer, Ruth, & Lavond, 1978), have demonstrated that lesions of the septal forebrain in Long-Evans hooded rats result in a marked increase in open-field gregariousness (contact time). Increased contact time has also been observed in adult animals following septal lesions produced in 7-day-old infant Long-Evans rats (Johnson , 1972).…”
mentioning
confidence: 88%